MODEL RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENINGKATKAN KEPERCAYAAN DIRI DISABILITAS NETRA “RA” - Marlina, Leni (Pekerjaan Sosial, 2015)
AbstractThe main problem that had been studied was not confident enough of visual disability student in the Outstanding School (SLBN A), Bandung. The problem of the RA’s subject was influenced by irrational thinking. Model of Rational Emotive Behavior Therapy (REBT) with the theory of A-B-C-D to exercise the way of thinking for subject to be more rational as well as homework assignment through against anxiety of subject was the intervention that had been used to strengthen the self-confidence.The objectives of this research is to assess the REBT model through the theory of A-B-C-D and homework assignment to strengthen the self-confidence of the subject. The research methodology was based on qualitative approach with action research design, which aims to solve the RA’s problem. In natural condition, researcher must comprehend, deep explore and empathize on each process, activity, procedure, attitude, sense as well as behavior of the subject in related to confidence aspect.The result of investigation revealed that REBT model through the theory of A-B-C-D and homework assignment can strengthen the self-confidence of subject. The subject was prone to alter its cognition and as a result the emotion and behavior is changed. RA’s subject tends to intensive in socializing with his friends, courageously to give an opinion, better and consecutively in daily activities such as washing his clothes, made the bed as well as cleared everything up. Based on this research, it is recommended that the family of subject could continue the exercise that has been programmed in order to nurturing the subject in his daily life. For the next research need the improvement to obtain the best approach.Keywords: Rational Emotive Behavior Therapy (REBT), self-confidence AbstrakPermasalahan yang dikaji adalah disabilitas netra yang mengalami ketidakpercayaan diri di SLBN A Kota Bandung. Ketidakpercayaan diri yang dialami oleh subjek RA disebabkan oleh adanya pemikiran irasional. Intervensi yang dilakukan adalah dengan menerapkan model Rational Emotive Behavior Theraphy (REBT) dengan teori A-B-C-D dan penugasan pekerjaan rumah.Tujuan penelitian adalah untuk mengakaji model REBT dengan teori A-B-C-D dan penugasan pekerjaan rumah dalam meningkatkan kepercayaan diri disabilitas netra. Metode penelitian menggunakan kualitatif dengan desain penelitian tindakan (action research). penelitian kualitatif dilakukan untuk menggali dan mengekplorasi makna dari suatu fenomena sosial yang terjadi. Eksplorasi makna yang didapatkan berada dalam seting alamiah yang tidak direkayasa. Action research merupakan suatu upaya mengujicobakan ide-ide ke dalam praktek untuk memperbaiki atau mengubah sesuatu agar memperoleh dampak nyata dari suatu situasi. Hasil penelitian menunjukan bahwa Rational Emotive Behavior Theraphy (REBT) yang dilakukan dapat meningkatkan kepercayaan diri “RA”. Hal ini dibuktikan dengan semakin seringnya “RA” berkumpul bersama teman-temannya, berani menyapa dan memulai percakapan. Subjek sudah memiliki inisiatif dan rasa tanggung jawab terhadap diri, Hal ini dibuktikan dengan adanya keteraturan dalam melaksanakan pekerjaan rumah seperti mencuci pakaian, membereskan tempat tidur, merapikan pakaian dan barang-barang. Pekerjaan ini dilakukan “RA” tanpa adanya perintah atau suruhan dari pembimbing asrama.Kata kunci: Rational Emotive Behavior Theraphy (REBT), kepercayaan diri